The Outback Re-Entry Device. A Pictorial Review. (August 2021) - Mulholland, Douglas; Thulasidasan, Narayanan; Patel, Ashish; Katsanos, Kostantinos; Diamantopoulos, Athanasios
The Outback™ Elite re-entry catheter (CORDIS, Cardinal Health, USA) is designed to facilitate placement and positioning of guidewires within the peripheral vasculature and allows for re-entry of a guidewire back into the true lumen of a vessel following a subintimal crossing of an arterial occlusion. The device was first introduced in 2005 and has become widely utilized in a variety of situations involving both arterial and venous interventions. This article aims to share our experiences with the Outback™ device and inform interventionalists of its utility and versatility.